Development and Validation of the Responsibility for Negative Thoughts Questionnaire - Saifpanahy , Pourya; Yarmohamadi Vasel, Shahryar; Yaghoobi , Abolghasem; Zoghi Paydar , Mohammad Reza (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective:  This study aimed to develop and psychometrically validate a questionnaire for assessing responsibility for negative thoughts.Methods and Materials: This descriptive-correlational instrument-development study used a researcher-developed 35-item questionnaire. The initial items were evaluated by six psychology professors and two educational sciences professors to determine their content validity and conceptual relevance. Construct validity was examined using exploratory factor analysis based on principal component analysis with varimax rotation. First- and second-order confirmatory factor analyses were subsequently conducted to assess the relationships between the items and their corresponding factors and between the identified factors and the overarching construct. Convergent validity was evaluated by examining the correlations between the developed questionnaire and the Jerabek Social Anxiety Scale. Internal consistency reliability was assessed using Cronbach’s alpha coefficients for the subscales and total questionnaire.Findings: The content validity ratio of the questionnaire was 0.91. The Kaiser–Meyer–Olkin coefficient was 0.88, and Bartlett’s test of sphericity was statistically significant, χ²(596) = 7,786.54, p < .001, confirming the suitability of the data for factor analysis. Exploratory factor analysis identified three factors with eigenvalues greater than 1.00, which collectively explained 70.18% of the total variance. First-order confirmatory factor analysis demonstrated an acceptable model fit, χ²/df = 2.53, GFI = 0.92, CFI = 0.94, IFI = 0.93, and RMSEA = 0.053. The second-order model also showed satisfactory fit, χ²/df = 2.45, GFI = 0.93, CFI = 0.94, IFI = 0.95, and RMSEA = 0.051. Thought control, magical thinking, compensatory behavior, and the total questionnaire score were significantly correlated with social anxiety, with coefficients ranging from 0.52 to 0.68 (p < .01). Cronbach’s alpha coefficients ranged from 0.89 to 0.93 for the subscales and were 0.94 for the total scale.Conclusion: The Responsibility for Negative Thoughts Questionnaire demonstrated a coherent three-factor structure, satisfactory convergent validity, appropriate model fit, and excellent internal consistency, supporting its use in psychological research and clinical assessment.